MANAJEMEN PROGRAM KELUARGA HARAPAN (PKH) TERHADAP PENGENTASAN KEMISKINAN DI KECAMATAN INDRAJAYA KABUPATEN PIDIE - Ramzijah Ramzijah; Mahrizal Mahrizal (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2021)
The purpose of this study was to examine the Hope Family Program Management (PKH) on poverty alleviation. The method used in this research was a quantitative method, with population of 49 villages with 735 respondents, with samples of 90 respondents with Slovin’s formula. The results of the research showed that the family of hope program (program effectiveness and fund management) has a positive and significant effect on poverty alleviation. So it can be concluded that with a program that runs effectively and the management of funds is right on target, the PKH program can run as desired, namely to reduce poverty levels.